Comparative study of vaginal danazol vs diphereline (a synthetic GnRH agonist) in the control of bleeding during hysteroscopic myomectomy in women with abnormal uterine bleeding: a randomized controlled clinical trial. (January 2016) - Sayyah-Melli, M.; Bidadi, S.; Taghavi, S.; Ouladsahebmadarek, E.; Jafari-Shobeiri, M.; Ghojazadeh, M.; Rahmani, V.
Abstract: Objective: To compare the usefulness of vaginal danazol and diphereline in the management of intra-operative bleeding during hysteroscopy. Design: Randomized controlled clinical trial. Setting: University hospital. Patients: One hundred and ninety participants of reproductive age were enrolled for operative hysteroscopy. Thirty women were excluded from the study. Interventions: One hundred and sixty participants with submucous myomas were allocated at random to receive either vaginal danazol (200 mg BID, 30 days before surgery) or intramuscular diphereline (twice with a 28-day interval). Main outcome measures: Severity of intra-operative bleeding, clarity of the visual field, volume of media, operative time, success rate for completion of operation and postoperative complications. Results: Overall, 145 patients completed the study. In the danazol group, 78.1% of patients experienced no intra-operative uterine bleeding, and 21.9% experienced mild bleeding. In the diphereline group, 19.4% of patients experienced no intra-operative uterine bleeding, but mild, moderate and severe bleeding was observed in 31.9%, 45.8% and 2.8% of patients, respectively. The difference between the groups was significant ( p < 0.001). A clear visual field was reported more frequently in the danazol group compared with the diphereline group (98.6% vs 29.2%, p < 0.001). The mean operative time was 10.9 min and 10.6 min in the danazol and diphereline groups, respectively ( p = 0.79). The mean volume of infused media was 2.0 L in both groups ( p = 0.99). The success rate was 100% for both groups with no intra-operative complications. Conclusion: Both vaginal danazol and diphereline were effective in controlling uterine bleeding during operative hysteroscopy. However, vaginal danazol provided a clearer visual field.